'Prevalence and antimicrobial susceptibility of Listeria monocytogenes and methicillin‐resistant Staphylococcus aureus strains from raw meat and meat products in Zaria, Nigeria. (1st March 2014) - Ndahi, M.D.; Kwaga, J.K.P.; Bello, M.; Kabir, J.; Umoh, V.J.; Yakubu, S.E.; Nok, A.J.
Abstract: The bacterial genera Listeria and Staphylococcus have been frequently isolated from food products and are responsible for a number of animal and human diseases. The aim of the study was to simultaneously isolate and characterize L. monocytogenes and Staphylococcus species from 300 samples of raw meat and meat products, to determine the susceptibility of the organisms to commonly used antimicrobial agents and to determine the presence of haemolysin A ( hyl) virulence gene in L. monocytogenes and staphylococcal cassette chromosome mec A (SCC mec ) gene in the Staph. aureus isolates using PCR. Of the 85 Listeria isolates tested, 12 L. monocytogenes were identified and tested for their sensitivity to 14 antimicrobial agents. All the 12 isolates (100%) were resistant to nine antimicrobial agents, but however sensitive to gentamicin. Only one isolate was found to harbour the hylA gene. Twenty‐nine isolates were confirmed as Staph. aureus by the Microbact 12S identification system and were all presumptively identified as methicillin‐resistant Staph. aureus species using oxacillin‐resistant Staph. aureus basal medium (ORSAB). The 29 Staph. aureus isolates were tested for their sensitivity to 16 antimicrobial agents, and 11 were resistant to methicillin. None of the 11 Staph. aureus isolates harboured the methicillin resistance, mecA gene. Significance and Impact of the Study: Listeria monocytogenes and Staphylococcus aureus are important agents of foodborne diseases. Occurrence of these infectious agents was established in meat and meat products in Zaria, Nigeria. Majority of isolates obtained from this study, displayed multidrug resistance to commonly used antimicrobial agents, including methicillin resistance among the Staph. aureus isolates. The potential virulence of L. monocytogenes found in ready‐to‐eat food was documented by the carriage of hly A gene by one of the isolates. A different mechanism of methicillin resistance or different homologue of mec A gene may be circulating among Nigerian isolates.